Strategi Komunikasi Internal PT Berca Kawan Sejati Surabaya Dalam Upaya Peningkatan Motivasi Kerja Akibat Isu PHK Karyawan - Hanif, Naufal Noor; Rini Ganefwati; Delmarrich Bilga Ayu Permatasari (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Bhayangkara Surabaya, 2025)
The purpose of this study was to see how PT Berca Kawan Sejati (BKS) Surabaya uses internal communication strategies to improve employee work motivation in response to the problem of layoffs (PHK) that emerged in the company environment. For this study, we conducted in-depth interviews with managers, team leaders, and employees of PT BKS Surabaya branch. The results showed that the company uses three main types of internal communication: downward (from superiors to subordinates), upward (from superiors to subordinates), and parallel (from subordinates to subordinates). One of these communication strategies is to use verbal and nonverbal communication, both formal and informal, and convey work motivation through briefings, internal meetings, and social interactions outside of working hours. However, PT BKS has demonstrated an internal communication strategy that is able to reduce concerns caused by the problem of layoffs and rekindle employees' desire to work. Keywords : Internal Communication, Work Motivation, Layoff (PHK), HR Management, Communication Strategy